Aplicações das integrais: - SOUSA, Cristiano Junis Santos (Universidade Federal do Tocantins, 2023)
In this work we approach some applications of integrals, where it is used within the thematic thought, the calculation of areas, volumes and the length of the arc. The problem consists in knowing what is the role of the study of integrals in solving everyday problems? Our goal is to verify the importance of integrals and their applications in situations and problems of the day to day. Thus, the research concerning the content of definite integrals is deepened, as well as the search for references about the topic. We present examples of applications of defined integrals. We also conducted the study from the point of view of Numerical Analysis on some integration methods and their simulations, in addition to the use of OCTAVE software in the implementa- tion of algorithms originated by Numerical Calculus methods. The methodology used is based on the qualitative approach as well as bibliographical research in books and articles.